Generation Z: Factors Influencing Online Purchase Behaviour In Kuala Lumpur And Selangor - Lee Yien Xing; Khaw Rou Ai; Uma Thevi Munikrishnan; Nurfaradilla Haron; Aeshah Mohd Ali; Nor Aziyatul Izni; Nur Ilyana Ismarau Tajuddin (RSIS International, 2025)
The "Shared Prosperity Vision 2030" and the Malaysia Digital Economy Plan predicted 500,000 jobs will be created and 22.6% of Malaysia's GDP will come from the digital sector. Therefore, the aim of this research is to assess the factors (price, e-commerce purchase experience, security, perceived risk, and perceived benefit) influencing online purchase behaviour among Generation Z in Kuala Lumpur and Selangor. The Theory Planned Behaviour (TPB) was used to analyse the human behavioural decisions. The theory asserted the three main elements (attitude, subjective norms, and perceived behaviour control) will affect certain behavioural intentions of individuals. Four hundred (400) questionnaires were distributed on a recommended sample for Generation Z at selected Private HEIs in Kuala Lumpur and Selangor. The set of data collected was examined using IBM SPPS (version 23) for data analysis. The findings of this research resulted in a significant influence of price and perceived benefit towards online purchase behaviour among generation Z. Overall, price was the most significant factor (β = .230; p = .000 < .05), followed by perceived benefit (β = .218; p = .000 < .05). Price ranked first because when making a comparison of price, results often show that for Generation Z to purchase these products online would be cheaper. Meanwhile, for perceived benefit, online shopping is preferred by Generation Z since it is more convenient than offline shopping.